Researching, installing dual fuel system to Ford Ranger diesel engine - Do, Văn Dũng; Nguyen, Văn Long Giang; Do, Khắc Phú (Journal of Technical Education Science, 2011)
Liquified petroleum gas (LPG) has been confirmed as one of preferably alternative fuels in the current situation. It contributes to the diversification of energy sources to replace and reduce pollution emissions from engines. However, it is necessary to carry out researches and experiments before applying extensively to practice. This paper presents the foundation of designing, the Diesel-LPG dual fuel system and experimental results. The study was conducted on Ford Ranger WL diesel engine. The test results show that the Diesel-LPG dual fuel engine consumes less fuel than the baseline Diesel engine while ensuring the basic features.